RESPONSIBILITY OF THE BOARD OF DIRECTORS FOR VIOLATIONS OF GOOD CORPORATE GOVERNANCE PRINCIPLES IN COMPANY MANAGEMENT - Thelisia Kristin; Amad Sudiro; Nicolaas Sugiharta (Indonesia Private Law Review)
The provisions of the Limited Liability Company Law have not yet set specific regulations governing the application of Good Corporate Governance (GCG) principles. The law requires companies to adhere to general corporate standards without detailing the specific forms, procedures, responsibilities, or sanctions associated with GCG. This lack of detailed regulation can lead to legal uncertainty. This paper employs a normative legal research method to explore how management responsibilities may arise in the event of GCG violations in the management of a limited liability company (PT). Such responsibilities may include both civil and criminal liabilities.